PERKEMBANGAN DAN EVALUASI KINEJRA REKSADANA TERBUKA KONTRAK INVESTASI KOLEKTIF DI INDONESIA - Catharina B Tan Lian Soei (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
There are four kinds of investment funds: Money Market Investment Funds, Income Investment Funds, Balanced or Discretionary Investment Funds and Equity Investment Funds which can give flexibility to investors, because each investment fund has different risks and rate of return. Investors who invest in Equity Investment Funds would expect higher returns over the long term but experience greater price variability than those who invest in the Balanced or - Income Investment Funds.It is important to evaluate performance of mutual funds based on risk and return analysis. The risk adjusted return approaches are Sharpe Ratio,' Treynor Ratio, Jensen's Differential Return.Research was carried out by investigating the daily fluctuation of Net Asset Value within 119 of Jakarta Stock Exchange (JSE) working days over 21 investment funds which had been issued before February 1997. The result shows that Balanced Investment Funds has lower risk compared to Equity' Investment Funds, but has the highest average rate of return among them.- Hypothesis testing (at 95% confidence level) shows that Income Investment Funds, Balanced Investment Funds and Equity Investment Funds have—' significant risk differentiation but have no significant average rate of return' - differentiation. Performance based on Sharpe Ratio, Traynor Ratio, and Jensen's Differential Return shows that Balanced Investment Funds is better than Equity Investment Funds. This is due to not only to the high rate of return but also to the lower variability of the return of fixed income securities, money market instrument as well as bonds. These intriguing results implied that fund managers could enhance investment fund return by diversifying across both fixed income securities, money market instruments, bonds and stocks. Clearly to say, a judicious mix of deposits, bonds, and stocks over time could be used as a means to potentially rise investment funds return while also reducing risk. This research is a preliminary one and is done in short period of time so that it may only give phenomenon in the short run.